From Stress Biology to Market Strategy: A Bioinformatics-Based Study of Biotic and Abiotic Factors Influencing Castor (Arandi) Cultivation in Arid Jaisalmer, Rajasthan - Bagchi, Preenon; Husain, Dildar; Tamboli, Yasir Ajeej; Singh, Ajeet; Pujari, Jitendra; Singh, Ashwani Kumar; Chouhan, Ganga Singh; Nathawat, Raghunandan Singh (Asian Journal of Biological and Life Sciences, 2026)
Background: Castor (Arandi) is an economically important oilseed crop with strong relevance to arid and semi-arid agriculture, particularly in western Rajasthan where climatic stress defines farming realities. The Jaisalmer district represents one of the harshest agro-ecological zones in India, characterized by extreme temperatures, erratic rainfall, salinity, and nutrient-poor soils. Understanding stress interactions is essential not only for crop resilience but also for strengthening the agricultural value chain and market outcomes for local communities. Materials and Methods: This study applies a Python-NGS pipeline to investigate genomic variation and stress-responsive gene expression in castor (Ricinus communis L.), a drought-tolerant oilseed crop of major industrial importance. Using publicly available RNA sequencing data (SRR23528831) from the NCBI database, a reproducible workflow was implemented to perform variant detection, transcript alignment, and differential gene expression analysis. Results: Variant analysis revealed polymorphic regions associated with regulatory and coding sequences linked to abiotic stress pathways. Differential expression profiling identified strong activation of genes involved in heat shock response, oxidative stress regulation, and osmotic balance. Gene Ontology enrichment further confirmed overrepresentation of pathways related to drought tolerance, protein stabilization, and abscisic acid signaling. Conclusion: These findings highlight a coordinated molecular defense system that enables castor to maintain cellular stability under extreme environmental pressure. Beyond biological interpretation, the study demonstrates how computational pipelines can inform agricultural decision-making. This approach supports the broader goal of climate-smart agriculture, where bioinformatics tools guide both scientific innovation and practical farming strategies.
Keywords: Castor (Arandi); Biotic and Abiotic Stress; Bioinformatics; Arid Agriculture; Crop; Management; Agricultural Marketing